Characterizing absolute lymphocyte count profiles in dimethyl fumarate–treated patients with MS: Patient management considerations. Issue 3 (June 2016) - Fox, Robert J.; Chan, Andrew; Gold, Ralf; Phillips, J. Theodore; Selmaj, Krzysztof; Chang, Ih; Novas, Mark; Rana, Jitesh; Marantz, Jing L.
Abstract: Background: Delayed-release dimethyl fumarate (DMF), indicated for the treatment of patients with relapsing-remitting multiple sclerosis (MS), is a disease-modifying therapy with potential immunomodulatory and neuroprotective effects. In clinical trials, DMF was associated with reduced white blood cell and absolute lymphocyte counts. Current US prescribing information recommends obtaining a complete blood count, including absolute lymphocyte count (ALC), before initiating and during DMF treatment. Methods: We conducted an integrated analysis of phase 2b/3/long-term extension studies of DMF in MS (N = 2, 470) to characterize ALC profiles. Results: Mean ALCs decreased by 30% during the first year and then plateaued, remaining above the lower limit of normal (LLN). Among patients treated ≥6 months (N = 2, 099), 2.2% experienced ALCs <500 mm 3 persisting ≥6 months. ALCs remained ≥LLN in 84% and 76% of patients during the first 6 and 12 months, respectively; of these, 0.1% and 0%, respectively, developed ALCs <500 mm 3 persisting ≥6 months at any time. Evidence of ALC improvement following DMF discontinuation was observed. DMF efficacy was not substantially different in patients with and without lymphopenia. Conclusion: Lymphocyte monitoring provides effective means for early identification of patients at risk for developing severe, prolonged lymphopenia.